Impact of anthropogenic activities on the biodiversity of macrobenthos and benthic ecological quality in the mudflats of Hwangdo Island, South Korea: field surveys and remote sensing assessments - Jian Liang; Chae-Woo Ma (Frontiers in Marine Science)
IntroductionAs coastal urbanization progresses, anthropogenic activities have significantly impacted mudflats. In South Korea, land reclamation and aquaculture have drastically altered mudflat ecosystems.MethodsIn our study, we utilized five remote sensing indices to assess the impact of anthropogenic activities on Hwangdo Island. We supplemented this with field surveys to evaluate macrobenthic biodiversity and benthic ecological quality, investigating their relationship to anthropogenic activities.Results and discussionSpearman’s correlation analysis revealed that terrestrial ecological quality influences macrobenthic biodiversity. The abundance of the predominant species, Pirenella sp., was primarily influenced by normalized differential build-up and bare soil index (NDBSI). Furthermore, biota-environment matching (BIO-ENV) analysis, distance-based multivariate analysis for a linear model (DisLM), and distance-based redundancy analysis (dbRDA) all pinpointed NDBSI as the predominant factor impacting macrobenthic communities in the mudflats of Hwangdo Island. Seasonal changes in NDBSI were mainly attributed to variations in bare soil area resulting from agricultural activities on Hwangdo Island. Overall, macrobenthic communities in the mudflats of Hwangdo Island are mainly indirectly affected by agricultural activities. Moreover, our study offers a fresh perspective on the conservation of Hwangdo Island’s mudflats and provides critical references for the South Korean government in crafting and implementing mudflat protection policies.